2021
DOI: 10.1108/er-01-2021-0009
|View full text |Cite
|
Sign up to set email alerts
|

Need to downsize? Your future employees may like the idea of cutting pay more

Abstract: PurposeStudies comparing the consequences of payroll cost reduction methods (i.e. cutting pay and downsizing) have been limited, with no studies comparing these methods' impact on job-seeker attraction. The current research tries to close this gap by comparing the effects of cutting pay and downsizing on job-seeker attraction outcomes.Design/methodology/approachTwo studies are conducted. The first study compares the effects of the two payroll cost reduction methods (i.e. cutting pay vs downsizing) on job-seeke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…An organization's total payroll cost (i.e., cost of salaries and wages) at a given point in time, thus, is the function of the number of workers that the organization utilizes and their pay rates. To reduce payroll costs, therefore, an organization can apply one or both of the following two methods (Yoon, 2022a(Yoon, , 2022b. First, the reduction can be achieved by decreasing the average pay rate of employees.…”
Section: Payroll Cost Reduction Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An organization's total payroll cost (i.e., cost of salaries and wages) at a given point in time, thus, is the function of the number of workers that the organization utilizes and their pay rates. To reduce payroll costs, therefore, an organization can apply one or both of the following two methods (Yoon, 2022a(Yoon, , 2022b. First, the reduction can be achieved by decreasing the average pay rate of employees.…”
Section: Payroll Cost Reduction Methodsmentioning
confidence: 99%
“…Therefore, the relationships that are observed in the studies may be stronger than they would otherwise be observed. However, as the main objective in these studies is to "compare" the effects of pay cut and downsizing on the outcomes of interests rather than to "estimate" these effects, this may be less of a concern (Yoon, 2022a(Yoon, , 2022b.…”
Section: Limitations and Future Studiesmentioning
confidence: 99%
“…Past studies on pay cuts/freezes Cutting (Freezing) pay is referred to as an act of an organization reducing (freezing) its employees' pay rates (Yoon, 2022) for often the same or similar amount and type of work that employees do. Employers may utilize the option of cutting (or freezing) pay, alongside the option of downsizing the number of employees, in needs of reducing payroll costs (Yoon, 2022).…”
Section: Theory and Hypothesesmentioning
confidence: 99%